2019
DOI: 10.15252/embr.201948109
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐11 counteracts mitochondrial ROS‐mediated clearance of Staphylococcus aureus in macrophages

Abstract: Methicillin‐resistant Staphylococcus aureus (MRSA) is a growing health concern due to increasing resistance to antibiotics. As a facultative intracellular pathogen, MRSA is capable of persisting within professional phagocytes including macrophages. Here, we identify a role for CASP11 in facilitating MRSA survival within murine macrophages. We show that MRSA actively prevents the recruitment of mitochondria to the vicinity of the vacuoles they reside in to avoid intracellular demise. This process requires CASP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 77 publications
4
53
0
Order By: Relevance
“…We also showed that IL‐6, KC, and TNF‐α are drastically reduced in the absence of caspase‐11 33 . Additionally, caspase‐11 −/− mice showed reduction in the level of IL‐1α and KC in response to MRSA infection 60 . Consequently, directly targeting caspase‐11/‐5 may reduce inflammation and limit the deleterious effects of senescent cells that accumulate during disease and aging 55 …”
Section: Il‐1α Is a Direct Substrate Of Mouse Caspase‐11 And Human Camentioning
confidence: 74%
See 4 more Smart Citations
“…We also showed that IL‐6, KC, and TNF‐α are drastically reduced in the absence of caspase‐11 33 . Additionally, caspase‐11 −/− mice showed reduction in the level of IL‐1α and KC in response to MRSA infection 60 . Consequently, directly targeting caspase‐11/‐5 may reduce inflammation and limit the deleterious effects of senescent cells that accumulate during disease and aging 55 …”
Section: Il‐1α Is a Direct Substrate Of Mouse Caspase‐11 And Human Camentioning
confidence: 74%
“…Using three different multiplicity of infections (MOIs), our group showed that caspase‐11 −/− macrophages promoted efficient clearance of methicillin‐resistant S aureus (MRSA) with increasing MOI. Further, lungs of caspase‐11 −/− mice exhibit reduced MRSA as compared to WT mice 60 . Thus, the in vivo and in vitro data suggest that the macrophage response against MRSA is more effective in the absence of caspase‐11.…”
Section: Pyroptotic and Non‐pyroptotic Anti‐bacterial Immune Surveillmentioning
confidence: 91%
See 3 more Smart Citations